"It's Just Always Eating": The Experiences of Young People Growing up Medium Chain Acyl-coA Dehydrogenase Deficiency. (August 2021) - Piercy, Hilary; Nutting, Charlotte; Yap, Sufin
Medium chain acyl-CoA dehydrogenase deficiency (MCADD) is a rare metabolic disorder, and commonly now part of newborn screening programs. Those diagnosed at birth are now progressing from childhood to adulthood. The study aim was to explore young people's experiences of living with MCADD and managing their condition. A descriptive qualitative study design involving semi-structured interviews with 12 participants aged 10 to 15 years, recruited from one regional pediatric metabolic disorder service in England. Data were analyzed using thematic analysis. The two major themes were "Eating for energy" and "Growing into a self-management role." Self-monitoring and self-management skills had been nurtured from early childhood by parents and healthcare providers. Young people's anxieties concerned having to maintain adequate energy input to stay safe and the associated burden of responsibility. Growing up with MCADD presents specific challenges. Self-management and ongoing support are important for dealing with those challenges.